Dietary Modulation and Clinical Outcomes During GLP-1 Receptor Agonist Therapy. A Literature Review - Rychlica, Kacper; Gawin, Konrad; Zawiślak, Wiktoria; Ignasiak, Anita; Cisowski, Michał; Dąbrowska, Maria; Cholewińska-Rychlica, Jolanta; Madura, Paulina; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) represent a major advancement in the treatment of obesity, type 2 diabetes mellitus, and cardiometabolic disease. Large randomized controlled trials have demonstrated that semaglutide and tirzepatide induce substantial and sustained reductions in body weight, improve glycaemic control, and reduce cardiovascular risk. As their clinical use expands, increasing attention has been directed toward the interaction between pharmacological appetite modulation and dietary behavior. Although GLP-1 RAs exert powerful effects on hunger, satiety, and gastric motility independent of dietary intervention, nutritional intake, meal structure, and food composition may influence treatment tolerability, nutrient adequacy, body composition, and long-term maintenance of weight loss. This narrative review synthesizes evidence from randomized trials, pharmacokinetic analyses, mechanistic reviews, and real-world studies to examine the physiological and clinical relevance of diet during GLP-1 receptor agonist therapy. Particular emphasis is placed on gastrointestinal tolerability, nutrient adequacy, preservation of lean body mass, pharmacokinetic constraints of oral formulations, cardiometabolic implications, and the challenges of long-term weight maintenance following treatment discontinuation.